Multiple Splenic Abscesses in a Child as a Complication of Typhoid Fever - Yüksel, Mürvet; Özkan, Keramettin Uğur; Bakarış, Sevgi (Fırat University, 2005)
Splenic abscess is a rare complication of typhoid fever in developing countries. Its clinical presentation is often non-specific. Here, we report a case of typhoid fever in a 12-year-old child with an unusual presentation; multiple splenic abscesses and review the literature for the complication of typhoid fever and the role of imaging findings in the diagnosis of splenic abscesses. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Dalak apsesi gelişmekte olan ülkelerde tifo ateşinin çok nadir bir komplikasyonu olarak görülmektedir. Bu tabloda klinik belirsiz karekterdedir. Biz burada, tifo ateşi geçirmiş ve çoğul dalak apsesi gelişmiş 12 yaşında bir çocuk hastayı sunuyoruz ve tifo ateşi komplikasyonlarını ve dalak apsesi tanısında görüntüleme yöntemlerinin rolünü literatur eşliğinde gözden geçiriyoruz. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Bir Çocukda Tifo Ateşi Komplikasyonu Olarak Multipil Dalak Apsesi